I feel psychologically stronger when my organization is socially responsible - Rego, Arménio (2017)
Literature suggests that psychological capital (PsyCap: self-efficacy, hope, optimism, resilience; Luthans et al., 2007) relates positively with important employee attitudes (e.g., organizational commitment), and multiple measures of performance, and negatively with undesirable attitudes (e.g., turnover intentions) and behaviors (e.g., deviance). However, few studies have considered the antecedents of this construct. Moreover, corporate social responsibility (CSR) has been primarily studied at the macro level, few studies having taken into account the individual level (Aguinis & Glavas, 2012). Adopting an individual level of analysis, this paper shows how the employees’ perceptions of CSR predict their PsyCap both directly and through the mediating role of positive affect and the sense of meaningful work.Two hundred and seventy-nine individuals (45% female; mean age: 37.3 years), working in 21 organizations operating in several sectors participated. The measures are: (a) perceptions of CSR (forty 7-point scales from Rego et al., 2011), (b) sense of meaningful work (four 5-point scalessuggested by Fry et al., 2005), (c) positive affect (three items adapted from Turban et al., 2009), and (d) PsyCap (twenty-four items from Luthans et al., 2007). Confirmatory factor analysis assessed the validity of the scales, and structural equation modeling was carried out to test the hypothesized model. The hypothesized model fits the data satisfactorily (e.g., RMSEA: 0.06), all paths being significant. The findings suggest that both positive affect and the sense of meaningful work partially mediate the relationship between the perceptions of CSR and PsyCap. They also suggest that the employees’ perceived inconsistency about several CSR dimensions may be detrimental to their sense of meaningful work, positive affect and PsyCap.The paper suggests that organizations may promote employees’ PsyCap by investing in CSR practices and ensuring that their employees perceive such practices. The paper contributes to understanding (a) the underlying mechanisms linking CSR with outcomes at individual level and (b) how organizations can harmonize organizational and employees’ interests/aims.